The influence of digital opinion leaders on consumer choices and demand elasticity in the Czech confectionary sector (2020–2024) - Mathieu, Sarah; Nebeská, Olga; Kotrba, Vojtěch; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2025)
The core hypothesis of the thesis is that the activity of digital opinion leaders in the Czech confectionery sector leads to a measurable increase in consumer purchasing decisions and reduces the price elasticity of demand for these products. The empirical research, based on a quantitative survey of N=100 Czech consumers, partially supported this hypothesis. The findings indicated that the emotional connection and sense of closeness consumers feel towards influencers is the strongest and most significant non-price determinant of demand. This emotional utility increases purchase intention and raises the acceptable price threshold, effectively making demand less price-sensitive and shifting the demand curve outward. However, the hypothesis was constrained by a critical boundary condition: the regression analysis showed that high exposure to influencer content actually had a significant negative effect on both purchase intention and willingness to pay. This suggested that excessive or repetitive content in this low-involvement market may induce advertising fatigue or skepticism, leading consumers to re-engage in price comparison and critical evaluation, thereby increasing price sensitivity.
Vedoucí práce: Olga Nebeská
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses